Neural processing of audiovisual and painful analogue trauma and its relationship with subsequent audiovisual and pain intrusions - Miedl, Stephan; Franke, Laila K.; Danböck, Sarah K.; Martini, Michael; Hettegger, Sabrina; Kronbichler, Martin; Flor, Herta; Wilhelm, Frank H. (European journal of psychotraumatology, 2024)
Background: Posttraumatic stress disorder and medically unexplained pain frequently co-occur. While pain is common during traumatic events, the processing of pain during trauma and its relation to audiovisual and pain intrusions is poorly understood. Objective: Here we investigate neural activations during painful analogue trauma, focusing on areas that have been related to threat and pain processing, and how they predict intrusion formation. We also examine the moderating role of cumulative lifetime adversity. Methods: Sixty-five healthy women were assessed using functional magnetic resonance imaging. An analogue trauma was induced by an adaptation of the trauma-film paradigm extended by painful electrical stimulation in a 2 (film: aversive, neutral) x 2 (pain: pain, no-pain) design, followed by 7-day audiovisual and pain intrusion assessment using event-based ecological momentary assessment. Intrusions were fitted with Bayesian multilevel regression and a hurdle lognormal distribution. Results: Conjunction analysis confirmed a wide network including anterior insula (AI) and dorsal anterior cingulate cortex (dACC) being active both, during aversive films and pain. Pain resulted in activation in areas amongst posterior insula and deactivation in a network around ventromedial prefrontal cortex (VMPFC). Higher AI and dACC activity during aversive>neutral film predicted greater audiovisual intrusion probability over time and predicted greater audiovisual intrusion frequency particularly for participants with high lifetime adversity. Lower AI, dACC, hippocampus, and VMPFC activity during pain>no-pain predicted greater pain intrusion probability particularly for participants with high lifetime adversity. Weak regulatory VMPFC activation was associated with both increased audiovisual and pain intrusion frequency. Conclusions: Enhanced AI and dACC processing during aversive films, poor pain vs. no-pain discrimination in AI and dACC, as well as weak regulatory VMPFC processing may be driving factors for intrusion formation, particularly in combination with high lifetime adversity. Results shed light on a potential path for the etiology of PTSD and medically unexplained pain. AI and dACC play a common role for both trauma- and pain-processing.In combination with high lifetime adversity, higher AI and dACC aversive film processing was associated with higher audiovisual intrusion frequency, whereas weaker AI and dACC pain discrimination enhanced the chance for pain intrusions.Weak regulatory VMPFC activity in aversive situations increased both audiovisual and pain intrusion formation. AI and dACC play a common role for both trauma- and pain-processing. In combination with high lifetime adversity, higher AI and dACC aversive film processing was associated with higher audiovisual intrusion frequency, whereas weaker AI and dACC pain discrimination enhanced the chance for pain intrusions. Weak regulatory VMPFC activity in aversive situations increased both audiovisual and pain intrusion formation.
Gesehen am 03.03.2025